2014
DOI: 10.1016/j.jvs.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Six-minute walk test closely correlates to “real-life” outdoor walking capacity and quality of life in patients with intermittent claudication

Abstract: The distance walked during the 6-minute walk test is closely correlated to outdoor walking capacity and health-related quality of life in IC patients. Our data support the use of 6MWD for routine clinical evaluation of walking capacity in IC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 28 publications
1
41
0
2
Order By: Relevance
“…4,24 Moreover, an improvement of walking distance does not necessarily equal increased physical activity levels in patients with IC, 6 and it lacks correlation with IC specific HRQoL. 5 Evidently, walking distance is an imperfect outcome parameter. Nonetheless, it is widely used in clinical trials, as its value in assessing treatment effect has been well established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,24 Moreover, an improvement of walking distance does not necessarily equal increased physical activity levels in patients with IC, 6 and it lacks correlation with IC specific HRQoL. 5 Evidently, walking distance is an imperfect outcome parameter. Nonetheless, it is widely used in clinical trials, as its value in assessing treatment effect has been well established.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 However, the clinical value of different outcome parameters in IC is currently under debate. Treadmill measured walking distances have been disputed for being an inadequate reflection of walking capacity in daily life, 4,5 and for failing to address actual physical activity limitations. 6 Additionally, walking distances correlate moderately with HRQoL measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community-based global positioning system (GPS) measurement has been recently proposed to assess outdoor walking capacity in PAD patients, that is, under conditions expected to be closer to real life. [3][4][5] Although an emerging approach, GPS assessment provides some interesting insights, adding arguments to the aforementioned controversies.…”
mentioning
confidence: 99%
“…Considering that an optimal functional test should directly correlate with patient-reported physical limitations, a recent study showed that patient-reported measures of walking limitation tended to correlate better with a GPS assessment of the maximal walking distance (MWD) than they do with the 6MWT and a graded TWT. 3 Regarding the agreement between GPS assessment and both TWT and 6MWT, available studies reported that GPS maximal 5 or total 4 walking distance was correlated to both TWT (r=0.81, P<0.001) and 6MWT (r=0.78, P<0.001). Median GPS MWD was reported to be on average 4.1 times higher than MWD from TWT.…”
mentioning
confidence: 99%